Using Behavioural Validity Method to Analyse the Dynamic Model of Smallholder Beef Farming Systems in Indonesia - Setianto, Novie Andri (ANIMAL PRODUCTION, 2016)
Abstract.  Smallholders beef farming is a complex systems which has wide range of stakeholders whose interests are varied. Systems thinking is one approach which can be recommended to study the complexity of a system.  Model is developed to mimic the situation of the farming situation in the real world.  A model opens up possibilities for simulating an intervention easier, less dangerously, and more ethically than experimenting in the real world.  However, before a model were used to simulate any intervention strategy, it needs to be validated.  This paper aimed to describe one validity method which used to test the validity of a model describing the smallholder beef farming.  A series of surveys have been undertaken to harness perspectives, opinion, and data from 2 beef farmers group in Kabupaten Banjarnegara and Kabupaten Banyumas.  Model were developed using iThink software developed by Ventana®.  Behavioural validity was conducted using extreme condition test which use 4 combination of extreme value; calving interval, share to farmer, purchasing price, and selling price.  Result showed that behavioural validity method using extreme value test was able to show the consistency of the logic which construct he structure of the model.